menu
bartleby
search
close search
Hit Return to see all results

the function g is defined as g(x)=2x^2-4x  find g(x-6)

Question

the function g is defined as g(x)=2x^2-4x  find g(x-6)

check_circleAnswer
Step 1

Given function is,

g(x) 2x2-4x
help_outline

Image Transcriptionclose

g(x) 2x2-4x

fullscreen
Step 2

To obtain g (x – 6), substitute x – 6 for ...

g(x-6)2(x-6)-4(x-6)
2(x-12x+36)-4(x) + 4(6)
=2x2 24x72 -4x 24
=2x2-28x96
help_outline

Image Transcriptionclose

g(x-6)2(x-6)-4(x-6) 2(x-12x+36)-4(x) + 4(6) =2x2 24x72 -4x 24 =2x2-28x96

fullscreen

Want to see the full answer?

See Solution

Check out a sample Q&A here.

Want to see this answer and more?

Our solutions are written by experts, many with advanced degrees, and available 24/7

See Solution
Tagged in

Math

Algebra

Other

Sorry about that. What wasn’t helpful?